2006
DOI: 10.1016/j.ceca.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein tyrosine phosphatase 1B by reactive oxygen species leads to maintenance of Ca2+ influx following store depletion in HEK 293 cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Reverse exchange was then initiated by the addition of NaCl subsequent to the addition of 350 M CaCl 2 ; this concentration of Ca 2ϩ was chosen to promote maximal Ca 2ϩ influx through the exchanger while minimizing influx due to capacitative Ca 2ϩ entry following internal Ca 2ϩ store depletion (discussed below). Activation of capacitative Ca 2ϩ entry in HEK293 cells typically requires the addition of millimolar concentrations of Ca 2ϩ (29,30), consistent with our observations (data not shown). Another modification we made in subsequent experiments was related to the observation that fluorescence amplitude levels attained using the described gramicidin clamp method were significantly higher than those previously obtained with intact cells (22) 2ϩ -ATPase (PMCA), the sarco/endoplasmic reticulum Ca 2ϩ -ATPase (SERCA), and mitochondria.…”
Section: Assaying For Nckx2 Reverse Exchange and Dependence On Internsupporting
confidence: 82%
“…Reverse exchange was then initiated by the addition of NaCl subsequent to the addition of 350 M CaCl 2 ; this concentration of Ca 2ϩ was chosen to promote maximal Ca 2ϩ influx through the exchanger while minimizing influx due to capacitative Ca 2ϩ entry following internal Ca 2ϩ store depletion (discussed below). Activation of capacitative Ca 2ϩ entry in HEK293 cells typically requires the addition of millimolar concentrations of Ca 2ϩ (29,30), consistent with our observations (data not shown). Another modification we made in subsequent experiments was related to the observation that fluorescence amplitude levels attained using the described gramicidin clamp method were significantly higher than those previously obtained with intact cells (22) 2ϩ -ATPase (PMCA), the sarco/endoplasmic reticulum Ca 2ϩ -ATPase (SERCA), and mitochondria.…”
Section: Assaying For Nckx2 Reverse Exchange and Dependence On Internsupporting
confidence: 82%
“…However, these compounds are also very potent phosphatase inhibitors and oxidants could thus regulate SOCE via increased phosphorylation. Indeed, several studies showed that maintenance of SOCE can be modulated by redox induced changes in phosphorylation [14,178,179]. On the other hand, Ehring et al reported that vanadate compounds act in a similar way as thimerosal: They deplete the ER Ca 2+ stores via thiol oxidation and thus induce activation of I CRAC independently of any kinases or phosphatases [180].…”
Section: Reactive Oxygen Species Effects On Soce and Crac/orai Channelsmentioning
confidence: 99%
“…An increase in the mitochondrial Ca 2+ concentration leads to increased ROS production which then may affect other redox sensitive signaling pathways [12,[14][15][16][17]. Further information on mitochondrial ROS production can be found in references [18][19][20][21][22].…”
Section: Mitochondriamentioning
confidence: 99%
“…Some of them implicate a co-regulation between ROS and Ca 2+ metabolism [6,7]. ROS can be produced intracellularly as a result of different signalling cascades including the activation of plasma membrane bound receptors, store operated Ca 2+ influx or UV light exposure [5,6,8].…”
Section: Introductionmentioning
confidence: 99%